The determinants of maximal speed adaptation during preseason in subelite female Australian rules footballers - Wijekulasuriya, G. A.; Canham, B.; Pane, C.; Dower, H.; Larkin, P. (International Journal of Sports Physiology and Performance, 2024)
Purpose Maximal speed is an important physical-fitness attribute for female Australian footballers. The effects of sprint training, maximal strength, and technical training have been reported in laboratory studies. However, no study has determined the combined effect and relative contribution of these training modalities on maximal speed adaptation in situ. Therefore, the aim of this study was to determine the training factors affecting maximal speed adaptation during a preseason in subelite female Australian Rules footballers.